Improvements in Orientation and Balancing Abilities in Response to One Month of Intensive Slackline-Training. A Randomized Controlled Feasibility Study - Dordevic, Milos; Hökelmann, Anita; Müller, Patrick; Rehfeld, Kathrin; Müller, Notger G. (Frontiers in Human Neuroscience, 2017)
Background Slackline-training has been shown to improve mainly task-specific balancing skills. Non-task specific effects were assessed for tandem stance and preferred one-leg stance on stable and perturbed force platforms with open eyes. It is unclear whether transfer effects exist for other balancing conditions and which component of the balancing ability is affected. Also, it is not known whether slackline-training can improve non-visual-dependent spatial orientation abilities, a function mainly supported by the hippocampus Objective To assess the effect of one-month of slackline-training on different components of balancing ability and its transfer effects on non-visual-dependent spatial orientation abilities. Methods Fifty subjects aged 18-30 were randomly assigned to the training group (T) (n=25, 23.2 ± 2.5 years; 12 females) and the control group (C) (n=25, 24.4 ± 2.8 years; 11 females). Professional instructors taught the intervention group to slackline over four consecutive weeks with three 60-minute-trainings in each week. Data acquisition was performed (within two days) by blinded investigators at the baseline and after the training. Main outcomes Improvement in the score of a 30-item clinical balance test (CBT) developed at our institute (max. score = 90 points) and in the average error distance (in centimeters) in an orientation test (OT), a triangle completion task with walking and wheelchair conditions for 60°, 90° and 120°. Results Training group performed significantly better on the closed-eyes conditions of the CBT (1.6 points, 95% CI: 0.6 to 2.6 points vs. 0.1 points, 95% CI: -1 to 1.1 points; p = 0.011, η_p^2 = 0.128) and in the wheelchair (vestibular) condition of the OT (21cm, 95% CI: 8 - 34cm vs. 1cm, 95% CI: -14 - 16cm; p = 0.049, η_p^2 = 0.013). Conclusion Our results indicate that one month of intensive slackline training is a novel approach for enhancing clinically relevant balancing abilities in conditions with closed eyes as well as for improving the vestibular-dependent spatial orientation capability; both of the benefits are likely caused by positive influence of slackline-training on the vestibular system function.